Penggunaan telehealth dalam meningkatkan kemandirian pasien gagal ginjal kronis dengan peritoneal dialysis (PD): A systematic review - Pasaribu, Yengsi Mei Karmita Br; Yulia, Yulia; Waluyo, Agung; Masfuri, Masfuri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: As the number of chronic kidney failure patients increases, the use of peritoneal dialysis (PD) is increasingly promoted because it has several advantages over the use of hemodialysis. Apart from several advantages of PD, there are complications that often occur such as peritonitis and lack of knowledge so that remote monitoring is needed to increase patient independence in carrying out treatment thereby increasing the satisfaction and quality of life of PD patients. Purpose: To determine the use of telehealth in increasing the independence of chronic kidney failure patients with peritoneal dialysis. Method: Qualitative research systematic literature review on the use of Telehealth in increasing the independence of chronic kidney failure patients on peritoneal dialysis. Article search sources used the Pubmed, Sage Journal, Scopus, Science Direct, and ProQuest databases. The total number of articles that entered the screening stage was 373 articles, and there were 10 articles that were categorized as eligible based on the inclusion criteria for this research. Results: Based on research and reviews of 10 selected articles, the results showed that Mobile Health or eHealth increases patient independence based on knowledge, the patient's ability to carry out PD treatment independently at home, increases compliance, satisfaction and improves the quality of life of chronic kidney failure patients with PD. Conclusion: The use of telehealth is effective in helping early detection of complications, such as peritonitis, as well as improving patient quality of life by reducing stress and feelings of isolation. However, the success of telehealth implementation is highly dependent on technological readiness, patient digital literacy, and data security and privacy. Suggestion: The use of Telehealth/Mobile Health is recommended as a non-pharmacological intervention that is easy to implement to increase the independence of chronic kidney failure patients with PD at home Keywords: Mobile Health; Peritoneal Dialysis; Self Management; Telehealth Pendahuluan: Peningkatan jumlah pasien gagal ginjal kronis semakin meningkat, penggunaan dialisis peritoneal (PD) semakin dipromosikan karena memiliki beberapa keuntungan dari pada penggunaan hemodialisis. Selain beberapa keuntungan PD, terdapat komplikasi yang sering terjadi seperti peritonitis dan pengetahuan yang kurang sehingga diperlukan pemantauan jarak jauh untuk meningkatkan kemandirian pasien dalam melakukan perawatan sehingga meningkatkan kepuasan dan kualitas hidup pasien PD. Tujuan: Untuk mengetahui penggunaan telehealth dalam meningkatkan kemandirian pasien gagal ginjal kronis dengan peritoneal dialysis. Metode: Penelitian kualitatif tinjauan literatur sistematis tentang penggunaan Telehealth dalam meningkatkan kemandirian pasien gagal ginjal kronis dengan dialisis peritoneal. Sumber pencarian artikel menggunakan database Pubmed, Sage Journal, Scopus, Science Direct, dan ProQuest. Total artikel yang masuk tahap screening sebanyak 373 artikel, dan artikel yang dikategorikan eligible berdasarkan kriteria inklusi penelitian ini diperoleh sebanyak 10 artikel Hasil: Berdasarkan telaah dan review dari 10 artikel pilihan, didapatkan hasil bahwa Mobile Health atau eHealth meningkatkan kemandirian pasien berdasarkan dari pengetahuan, kemampuan pasien melakukan perawatan PD secara mandiri dirumah, peningkatan kepatuhan, kepuasan serta peningkatan kualitas hidup pasien gagal ginjal kronis dengan PD. Simpulan: Penggunaan telehealth efektif dalam membantu deteksi dini komplikasi, seperti peritonitis, serta meningkatkan kualitas hidup pasien dengan mengurangi stres dan rasa isolasi. Meski demikian, keberhasilan implementasi telehealth sangat bergantung pada kesiapan teknologi, literasi digital pasien, serta keamanan dan privasi data. Saran: Penggunaan Telehealth/Mobile Health direkomendasikan sebagai salah satu intervensi non farmakologi yang mudah diterapkan untuk meningkatkan kemandirian pasien gagal ginjal kronis dengan PD di rumah. Kata Kunci: Dialisis Peritoneal.; Kemandirian Pasien; Mobile Health; Telehealth.